What is ab initio in nuclear theory? - Ekström, A.; Forssén, C.; Hagen, G.; Jansen , G. R.; Jiang, W.; Papenbrock, T. (Frontiers in Physics, 2023)
Ab initio has been used as a label in nuclear theory for over two decades. Its meaning has evolved and broadened over the years. We present our interpretation, briefly review its historical use, and discuss its present-day relation to theoretical uncertainty quantification.